Board characteristics, firm performance, and institutional ownership: Evidence from listed companies of Pakistan - Fadia Naz; Hisham Bin Mohammad; Chai Aun Ooi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2026)
This study endeavors to scrutinize the impact of board characteristics on firm performance directly as well as through the moderating influence of institutional ownership. Tobin' Q and market-to-book ratio are the proxies of firm performance as dependent variable. The analytical approach involves unbalanced panel data comprising 883 firm year observations of 75 textile manufacturing firms listed on Pakistan Stock Exchange from 2012 - 2023 by using fixed effect regression and system GMM estimation techniques through STATA software. Notably, findings indicate that board size and female directors demonstrate significant positive influence, whereas, outside directors and director ownership shows significant negative influence on firm performance. Furthermore, findings also indicate that institutional ownership has a significant positive moderating influence on the relationship between board characteristics and firm performance. This contribution to the scholarly literature provides certain important theoretical insights and practical implications for practitioners and policy makers.
Keywords: 330; Board characteristics; firm performance; institutional ownership; ownership structure; Pakistan Stock Exchange